Morphological and molecular characterization of Lepidonema magnum Morffe & García, 2010 (Nematoda: Oxyuridomorpha: Hystrignathidae) from Passalus interstitialis Eschscholtz, 1829 (Coleoptera: Passalidae) from Cuba and new locality records for the species - Morffe, Jans; García, Nayla; Breugelmans, Karin; Hasegawa, Koichi; Davis, Andrew K. (Zootaxa, 2019)
Lepidonema magnum Morffe & García, 2010 (Nematoda: Oxyuridomorpha: Hystrignathidae) is redescribed and illustrated with the aid of SEM. New features of the cephalic end and genital tract of the females were observed. New locality records are given. The phylogenetic position of the species is inferred on the basis of the D2-D3 segment of the 28S LSU rDNA and 18S SSU rDNA. L. magnum forms a monophyletic clade formed by other hystrignathids: Coynema poeyi (Coy, García & Álvarez, 1993), two species of Longior Travassos & Kloss, 1958 and two Hystrignathus Leidy, 1850.